Silica-lipid hybrid microparticles as efficient vehicles for enhanced stability and bioaccessibility of curcumin - Ma, Yudi (Array, 2019)
Curcumin is an active ingredient with multiple functions, but its application is often restricted due to its poor water solubility, weak stability, and consequently low bioaccessibility. Based on this, the aim of this work is to develop a new vehicle to overcome these restrictions. Here we developed a curcumin-loaded nanoemulsion and then curcumin-loaded silica-lipid hybrid microparticles through emulsification and vacuum drying, respectively. The loading of curcumin in the nanoemulsion and microparticles was (0.30±0.02) and (0.67±0.02) %, respectively. FTIR and XRD analyses of microparticles revealed that curcumin was encapsulated in porous, amorphous silica. In vitro antioxidant activities showed that the encapsulation would not affect the antioxidant activity of curcumin. In vitro simulated digestion indicated that nanoemulsion and microparticles had higher curcumin bioaccessibility than the control group. The storage stability of microparticles remained the same during 6 weeks in the dark at 4, 25 and 40 °C. Moreover, the microparticles had a better chemical stability than nanoemulsion under the light. The cell viability was over 80 % when the concentration of nanocarriers was less than 45 μg/mL. Hence, the microparticles could be a promising means to load curcumin and improve its solubility, light stability and bioaccessibility.